Construcciones simbólicas de la guaria morada en la poesía de Lisímaco Chavarría - Villalobos Villalobos, Carlos Manuel (2013)
The declaration of the purple orchid as national flower of Costa Rica is based in the literary discourse. This paperanalyzes the presence of the purple orchid in the work of the Costa Rican poet Lisímaco Chavarría. The symbolicfunction of the flower is analyzed as representation of the idealized woman and the desire.